2021
DOI: 10.3892/ol.2021.12674
|View full text |Cite
|
Sign up to set email alerts
|

Role of cancer‑associated fibroblasts in the resistance to antitumor therapy, and their potential therapeutic mechanisms in non‑small cell lung cancer (Review)

Abstract: Non-small cell lung cancer (NSCLC) is a malignant tumor with high morbidity and mortality rates, which seriously endangers human health. Although treatment methods continue to evolve, the emergence of drug resistance is inevitable and seriously hinders the treatment of NSCLC. The tumor microenvironment (TME) protects tumor cells from the effects of chemotherapeutic drugs, which can lead to drug resistance. Cancer-associated fibroblasts (CAFs) are an important component of the TME, and various studies have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Our understanding of the role of the tumor microenvironment (TME) over the recurrence and relapse of cancer has been growing in the last years. The physical properties and composition of the TME generate signals to alter cancer cell proliferation and migration [1,2] and it is thought that the TME could represent a protective niche for tumoral cells during antitumoral therapies [3,4]. The extracellular matrix (ECM) is one of the most relevant elements that compose the TME [5] and it represents a scaffold structure for cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the role of the tumor microenvironment (TME) over the recurrence and relapse of cancer has been growing in the last years. The physical properties and composition of the TME generate signals to alter cancer cell proliferation and migration [1,2] and it is thought that the TME could represent a protective niche for tumoral cells during antitumoral therapies [3,4]. The extracellular matrix (ECM) is one of the most relevant elements that compose the TME [5] and it represents a scaffold structure for cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma is one of the most CAF-rich cancers. The role of CAFs in resistance to chemotherapy of lung adenocarcinoma is well appreciated [167,168]. Cisplatin treatment increases Interleukin-11 (IL-11) levels in CAFs which protects lung adenocarcinoma cells from apoptosis [169].…”
Section: Interleukins Secreted By Cafsmentioning
confidence: 99%
“…Indeed, it has been found that Yes-associated protein (YAP) and the transcriptional coactivator with PDZ-binding motif (TAZ) that belong to the Hippo pathway are activated in lung fibrosis. To this purpose, Xu et al through single-cell RNA sequencing found that the YAP/TAZ, TGF-β, Wnt, and the PI3K axis were activated in the AECs of IPF patients [152,153]. They suggested that mTOR/PI3K/AKT signalling contributed to IPF pathogenesis, both increasing the proliferation of lung epithelial cells and lung fibroblasts.…”
Section: The Onset and Progression Of Ipf: The Leading Role Of Tgf-β1mentioning
confidence: 99%